Red blood cell alloimmunization in sickle cell disease patients in Uganda - Natukunda, Bernard; Schonewille, Henk; Ndugwa, Christopher; Brand, Anneke (Transfusion, 2010)
BACKGROUND: Blood transfusion is an integral part in the management of sickle cell disease (SCD) patients. Alloimmunization is a recognized complication of red blood cell (RBC) transfusions with consequences including delayed hemolytic transfusion reactions and difficulties in getting compatible blood for future transfusions. The objective of this study was to determine the frequency of RBC alloimmunization in SCD patients in Uganda where pretransfusion screening for alloantibodies is not practiced. STUDY DESIGN AND METHODS: In a cross-sectional study, SCD patients at Mulago Hospital Sickle Cell Clinic, Kampala, Uganda, were investigated. The demographic characteristics and transfusion history were recorded. Blood samples were drawn from consenting, previously transfused patients and RBC alloimmunization was demonstrated using immunohematologic techniques. RESULTS: There were 428 patients (median age, 12 years; female/male ratio, 1.0) and they had received a median of 3 units in a median of three transfusion episodes. Twenty-six patients (6.1%) possessed RBC alloantibodies and 21 (80.7%) of them had received up to 10 transfusions. A total of 30 alloantibodies was found; 20 (66.7%) and 5 (16.6%) belonged to Rh and MNS blood groups, respectively. Five of the alloimmunized patients had multiple antibodies. CONCLUSIONS: The rate of RBC alloimmunization in Ugandan SCD patients was 6.1%. The homogeneity between donors and SCD patients plus the low transfusion load may explain this immunization frequency. Nevertheless, our study confirms the significance of RBC alloimmunization as a complication in Ugandan SCD patients. Therefore, there is need to improve immunohematologic testing in Uganda so that RBC alloimmunization and its consequences may be prevented.
Keywords: Red blood cell; Alloimmunization; sickle cell disease patients; Uganda